(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Flavonoids are widely dispersed secondary metabolites that are currently present in high concentrations in the average person’s diet. The most recent data, the majority of which have been published in Phytotherapy Research, are highlighted in this article along with some of the most recent advancements in the pharmacology of flavonoids and related polyphenolic compounds. These data highlight new flavonoid anti-inflammatory, antilipidemic, antihyperglycemic, antiviral, hepatoprotective, gastric antiulcer, cardioprotective, neuroprotective, antioxidant, and anticancer actions. These latest findings support the perspective for a therapeutic use and support the various positive pharmacological activities that have long been recognised.